Upaya untuk Peningkatan Pemahaman Pendidikan Seks Islami Melalui Film Animasi Bagi Siswa ABK Kelas IV di MI Ma’arif Kemangguan - Khoeriyah, Faridatul; Fatimah, Siti (IAINU Kebumen, 2024)
Sex education for children with special needs is now a necessity. Because basically sex education is a preventive effort so that every child with special needs can recognize, understand and manage biological developments and changes in himself, respect other people’s sexual behaviour, and not get caught up in deviant sexcual behavior or get violence and sexcual harassment from other people. Because elong with problematic physical and psychological condition, children with special needs are easily manipulated, seduced, so that they are often treapped to be used as objects of lust by people with bad personality. They purpose of this study was to determini the increase in understanding of Islamic sex education through animated films for fourth grade ABK students at MI Ma’arif kemangguan sub-district. Alian,keb. Kebumen. This research includes PTK research ( classroom Action Research ), data collection techniques used namely and interviews on the results of the study found that the application of islamic sex eduation through animated films can improve development and apply it in their environment, for students with special needs azfa fawaidul ulum. And carried out according to the RPP that has been made. The results of the analysis show an increase, namely in cycle i there are 2 meetings, namely meeting 1 gets 33,33% and meeting 2 in cycle I gets 40% completeness, and increases in cycle II meeting 3 53,3% of they 2 and meeting 73,33% so it can be concluded that animated film media improves the development of students with special needs in Islamic sex education.